Mitigation of ground vibrations using geocells: a mini-review - Hegde, Amarnath (Frontiers in Built Environment, 2024)
This manuscript presents a mini review on the potential new application of geocell in the mitigation of ground vibration. An effort has been made to provide a detailed quantification and mechanisms involved in the vibration isolation performance of geocells. The latest studies on the topic are summarized in three sections, namely, experimental, numerical, and analytical studies. Details on the optimum dimension of geocells, depth of placement, and suitable infill materials for effective isolation of vibrations have been covered. Further, the mechanism responsible for the superior vibration isolation performance of the geocells is highlighted. In addition, analytical equations and machine learning-based models for predicting the isolation performance of the geocells are discussed. The study reveals that geocell is very effective in isolating ground vibrations as compared to other forms of geosynthetics. Geocells were found to enhance dynamic properties and reduce the amplitude of vibrations significantly.